Liquid smoke effects on Escherichia coli O157:H7 in beef trimmings and ground beef patties - R. Estrada-Munoz; Elizabeth A.E. Boyle; James L. Marsden (Kansas Agricultural Experiment Station Research Reports, 1997)
Liquid smoke (LS) reduce d Escherichia coli O157:H7 counts in inoculated beef trimmings and ground beef patties. The counts were reduced (P<.05) by .5 log 10 cfu/g immediately after beef trimmings were treated with 8% LS and by 1.2, 2.0, 1.6, and 2.3 log 10 cfu/g after the trimmings were formed into patties and tested or stored under refrigeration for 1, 2, and 3 days, respectively (2 log10 reduction represents 99%) Thus, LS could make beef-containing products safer with respect to foodborne pathogens.
Keywords: Cattlemen' s Day; 1997; Kansas Agricultural Experiment Station contribution; no. 97-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 783; Beef; Liquid smoke; Escherichia coli O157:H7; Ground beef